Understanding the links between agriculture and health: Urban Agriculture and Health - Lee-Smith, Diana; Prain, Gordon (International Food Policy Research Institute, 2006)
With half the world’s population living in cities and towns, many poor urban dwellers face problems gaining access to adequate supplies of nutritionally balanced food. For many urban populations, an important source of food is urban and peri-urban agriculture (UPA). Production and processing of crops—particularly horticultural crops—and livestock is frequently part of urban and peri-urban livelihood strategies, and the food produced forms a large part of informal sector economic activity. This brief examines the benefits and problems of UPA for the nutrition and health of poor urban and peri-urban populations... An adequate health-impact assessment of urban agriculture is still incomplete.Research questions remain concerning the level of chronic disease risk posed by contamination of urban food from air pollution, as well from industrial effluents. Further assessment is needed of the health risks of using biological wastes as fertilizer. Research questions also remain regarding the infectious disease risks posed by urban livestock keeping... Adequate waste treatment systems and sanitation need to be provided to poor countries’ urban areas, but the technologies should be designed to capture the nutrients in waste for increased food production. Control of discharges into soil, air, and water by industries, whether large factories or small kiosks, is likewise essential. Existing environmental legislation needs to be made effective by proper implementation through both community action and government support in urban neighborhoods.